Loyaume and Νomarchie: Κeywords of the French revolution in the Greek vocabulary - Sfoini, Alexandra (The Historical Review/La Revue Historique, 2014)
The French Revolution was the occasion for the reformulation of the definitions of basic concepts as liberté, égalité, fraternité, nation, patrie, etc. At the same time a lexical creativity, a large quantity of words appeared, some of them total news or with new significations, temporary or persistants (aristocruche, humanicide, enragés, loyaume, etc.). This paper examines aspects of lexical and semantic developments in Greek language focussing on the era of the French Revolution. This important period was characterized by intensified contacts with Western Europe. In this process, Greek intellectuals expressed an open admiration of the new French model of the nation in their political works and attempted to form a new political language. Most of the modern notions were introduced from the French language, which in his turn had acquired a large amount of greek-latin loan words. The intercultural dimension provide the tools for analysing the ways in which the new terms and concepts were transfered to the greek vocabulary. These processes are examined as reflected in the Hellenic Nomarchy (Italy 1806), a crucial text of the period.